Hypomelanosis of Ito: ultrastructural study. - Schepis, C.; Cavallari, V.; Elia, M.; Ussia, A.F.; Pontieri, F. (European Journal of Pediatric Dermatology, 2018)
A 7-year-old girl with lto syndrome and complex neurologic disorders is reported. The histologic and ultrastructural examination of a skin biopsy demonstrated, in hypopigmented areas, a reduction of number and size of melanosomes in basal keratinocytes. In addition, mild regressive changes of melanocytes were observed. No changes were demonstrated in Langerhans cells as well as nerve fibres. Namely, no relationships were observed between nerve endings and melanocytes.